The impact of problem-based learning in the writing of descriptive texts with students of first year of bachillerato at a public high school, academic period 2021-2022. El impacto del aprendizaje basado en problemas en la escritura de textos descriptivos con los estudiantes de primero de bachillerato en un colegio público, del periodo académico 2021-2022. - Rivera Berru, Jessica Vanessa (2022)
The main objective of this research study was to demonstrate whether problem-based learning improves the writing of descriptive texts of the students of First Year of Bachillerato at a public high school of Ecuador during the academic period 2021-2022. This research used a quasi-experimental method. Therefore, the quantitative data was collected by using a pre-test and post-test. Likewise, a survey was useful to record 16 students’ feelings and perceptions towards problem-based learning. Based on the results of the pre-test and post-test, the students had a significant improvement in the writing of descriptive texts which was evident through its indicators: vocabulary, chronological order, and mechanics. The application of problem-based learning helped students to feel more comfortable and collaborative in classes, also they promoted the students’ cooperation, and motivated them to participate more actively in the classroom. Additionally, it was evident that with the implementation of problem-based learning students developed critical thinking skills, which allows them to think about something they want to understand and do it in the best possible way, appreciating and evaluating the process in order to make decisions when they write descriptive texts. Keywords: problem-based learning, descriptive texts, problem-solving skills, communicative skills, critical thinking.